Inventory Accounting Analysis at PT. XYZ - Galatea Yolanda Oktaviani; Hendra Dwi Prasetyo (INCOME: Innovation of Economics and Management, 2022)
In trading companies there are assets obtained from purchases or from their own production with the aim of being resold to consumers, namely inventory. This led the author to investigate whether the use of inventory accounting at PT. XYZ adhered with PSAK No. 14 governing supplies. The authors employed a qualitative descriptive technique in their study, which included data collection and processing. The data used are both primary and secondary. The data was collected, processed, and analyzed before being presented in detail. This analysis makes use of data from 2019. The findings reveal that PSAK no. 14 was appropriately implemented, including inventory recording by PT. XYZ, which is a perpetual recording and inventory valuation using FIFO (First in First Out), which is in compliance with accounting rules.